TI_GERICHTE 15.2013.114 vom 27. Februar 2014 , Annullamento di asta. Ricorso di un interessato. Difetto di legittimazione - TI Tribunale d'appello (2014)
Annullamento di asta. Ricorso di un interessato. Difetto di legittimazione